Photosensitizer–AgNP composite with an ability to selectively recognize pathogen and enhanced photodynamic efficiency. (28th September 2017) - Zhang, Jiaqi; Lu, Zhentan; Yu, Zhenguo; Zhong, Weibing; Jiang, Haiqing; Zhao, Qinghua; Li, Fei; Zhang, Xinge; Wang, Dong
Abstract : A photosensitizer–AgNP composite could recognise bacteria smartly and showed greater photodynamic efficiency than did the free photosensitizer. Abstract : BODIPY-functionalized glycopolymer-modified AgNPs were prepared as a PDT agent. The agent was "smart", i.e., it could distinguish pathogens from normal cells, and showed a photodynamic efficiency three times greater than that of free photosensitizer under the same light intensity. The work is a good attempt to make a new generation of PDT agents for antibacterial applications.